2023
DOI: 10.21203/rs.3.rs-3079466/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Efferocytosis is restricted by axon guidance molecule EphA4 via ERK/Stat6/Mertk signaling following brain injury

Eman Soliman,
John Leonard,
Erwin Kristobal Basso
et al.

Abstract: Background Efferocytosis is a process that removes apoptotic cells and cellular debris. Clearance of these cells alleviates neuroinflammation and prevents the release of inflammatory molecules and promotes the production of anti-inflammatory cytokines to help maintain tissue homeostasis. The underlying mechanisms by which this occurs in the brain after injury remains ill-defined. Methods We demonstrate using GFP bone marrow chimeric knockout (KO) mice, that the axon guidance molecule EphA4 receptor tyrosine … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Efferocytosis, the process of clearing dead cells, is crucial for resolving inflammation and promoting tissue repair after TBI [6]. Our previous studies have shown an upregulation of "find-me" signal receptors (S1pr1 and Cx3cr1), engulfment receptor (MerTK), and bridging molecules (Gas6 and Pros1) in the damaged cortex, indicating active efferocytosis after trauma.…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…Efferocytosis, the process of clearing dead cells, is crucial for resolving inflammation and promoting tissue repair after TBI [6]. Our previous studies have shown an upregulation of "find-me" signal receptors (S1pr1 and Cx3cr1), engulfment receptor (MerTK), and bridging molecules (Gas6 and Pros1) in the damaged cortex, indicating active efferocytosis after trauma.…”
Section: Discussionmentioning
confidence: 95%
“…This emerging concept suggests that skull-bone marrow cells may be crucial in modulating brain homeostasis and neuroinflammation, particularly following injuries. While it is well-established that TBI disrupts the blood-brain barrier, leading to immune cell infiltration from the bloodstream [6,22], the proportion and the identity of immune cells that migrate from skull bone marrow to brain parenchyma after injury remain uncertain. Using the calvarium bone-flap transplantation technique and controlled cortical impact (CCI) model of TBI, our study aimed to investigate whether calvarium-derived immune cells infiltrate the brain following TBI and differentiate them from their blood-derived counterparts.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations